Implementation of Cloud-Based Information Management to Enhance Work Efficiency in Information Technology Companies - Widjaja, Andree Emmanuel; Mulyati, Mulyati; Supriyanti, Dedeh; Hikam, Ihsan Nuril; Goestjahjanti, Francisca Sestri; Kamar, Karnawi; Nathalie, Julia (International Transactions on Artificial Intelligence, 2025)
In the era of rapid digital transformation, Information Technology (IT) companies are increasingly challenged to manage large and complex datasets efficiently. This study investigates the implementation of cloud-based information management systems as a strategic approach to improving work efficiency within IT companies. A mixed-method approach was adopted, combining quantitative data from system performance metrics and employee productivity reports with qualitative insights obtained from surveys and in-depth interviews with employees and managers. The results show a significant improvement in work efficiency, with a 30% decrease in system response time and a 25% increase in employee productivity. Additionally, qualitative findings indicate enhanced employee satisfaction, better collaboration, and more effective decision-making due to improved data accessibility and streamlined workflows. The integration of cloud-based systems with existing IT infrastructure is also identified as a critical factor for the success of such implementations. These findings highlight that cloud technology not only addresses operational challenges but also supports broader strategic goals. The study recommends IT companies invest in employee training, robust data security measures, and seamless integration strategies to fully leverage the potential of cloud-based information management in optimizing performance and maintaining competitiveness.